A DECISION-THEORETIC APPROACH TO MAINTAIN TRUST IN UBIQUITOUS DISPLAYS ENVIRONMENTS - Kurdyukova, Katja; André, Elisabeth; Leichtenstern, Karin (International Journal of Computing, 2010)
In this paper, we present a decision-theoretic approach to trust management for ubiquitous display environments that assesses the user’s trust in a system, monitors it over time and applies appropriate measurements to maintain trust in critical situations. The approach has been applied to two interactive applications that have been developed as part of a university-wide ubiquitous displays management system. The two applications run on public display located in public rooms at Augsburg University. They can be operated and assisted by mobile phones. In the paper, we define decision policies for the two applications and investigate their impact on relevant trust factors, such as privacy, comfort of use, transparency and controllability.